Hubungan Hasil Pemeriksaan Kultur Urin terhadap Hasil Protein dan Berat Jenis Urin sebagai Pemeriksaan Fungsi Ginjal pada Pasien Infeksi Saluran Kemih - Supriyanti, Ispi; Agrijanti; Ari Khusuma; Lalu Srigede (Poltekkes Kemenkes Mataram, 2025)
Background : Laboratory examination for UTI consists of urine culture and dipstick urinalysis consisting of glucose, protein, bilirubin, urobilinogen, erythrocytes, pH, ketones, specific gravity, leukocytes and nitrites. In this study, only protein and urine specific gravity were examined, because one of the causes of proteinuria is post-renal which occurs due to infection in the urinary tract. Meanwhile, for urine specific gravity, patients who are suspected of having a urinary tract infection usually have a high urine specific gravity due to an increase in the number of leukocytes in the urine. UTI can cause a decrease in kidney function due to the risk of infection in the ureters which can cause several complications of kidney disease. Research Objective : To find out whether there is a relationship between the results of urine culture examination and the results of protein and specific gravity of urine as an examination of kidney function in UTI patients. Research Method : This research is an analytical observational research with a cross sectional research design. By examining urine culture and urinalysis using the dipstick method and analyzed using the chi square test. Results of the study : The results of data analysis showed a significant relationship in the positive direction with the strength of the relationship being quite strong between urine culture examination and urine protein results in UTI patients (p 0.030˂0.05). And there is a significant relationship in the positive direction with the strength of the relationship being quite strong between urine culture examination and urine specific gravity results in UTI patients (p 0.021<0.05). Conclusion : There is a significant relationship in the positive direction with the strength of the relationship being quite strong between the results of the protein examination and the urine culture results in UTI patients, as well as the results of the specific gravity examination and the strength of the urine culture results in UTI patients, there is a significant relationship in the positive direction with the strength of the relationship being quite strong.